Impact of food nutrition intervention on food handlers’ knowledge and competitive food serving: a randomized controlled trial - Noor Izani N. J. (2018)
The aim of this study was to evaluate the impact of Food Nutrition Intervention (FNI) for improving food handlers’ knowledge and serving of competitive food in the primary school canteens. We randomized 16 out of 98 primary schools into intervention and control groups using a multistage sampling method. The training programme for the intervention group and questionnaires for evaluating knowledge were developed. On-site observations were done to document all competitive foods served in school canteens. Out of the 79 food handlers who participated in this study, 33 (41.8%) were in the intervention group and 46 (58.2%) were in the control group. The majority of food handlers were female, Malay, had education at middle levels, and at middle-aged. The commonest food category served was carbohydrate (75%), high-fat foods (34.4%) and food not recommended for sale (34.4%). Knowledge about healthy food choice in the intervention group at 6 weeks and 12 weeks post intervention were significantly higher than at baseline. The intervention group also demonstrated significantly better knowledge composite score at 6 weeks and 12 weeks following intervention. These improvements were also observed between intervention and control regardless of time. By six weeks, the number of vegetable menu served significantly increased in the intervention (p=0.040) and by 12 weeks, the number of milk and milk products served also significantly increased (p=0.015) as compared to the control group. Thus, the provision of FNI was associated with significantly improved healthy food knowledge amongst food handlers, the serving of vegetables and milk or milk products in school canteens.